Silicon-mediated mitigation of cadmium risk in peanut-growing soil depends on cultivar-specific defense strategies - Nengde Zeng; Guowei Cao; Mingda Liu; Yuan Hu; Yaojing Wang; Mengyuan Ni; Na He; Wanting Ling; Hongtao Zou; Dan Yang (Applied Soil Ecology, 2026)

Microplastic contamination of agricultural soil in Southern India: a review and PRISMA analysis - Teena Hephzibah Nancy Inbaraj; Bahati Shabani Nzeyimana; Jefrin Luee Moses; Sharly Elgal Nirmal; Sheela Mary Mariyaselvam (Environmental Monitoring and Assessment, 2026)

Molecular and morphological identification methods show contrasting trends in soil fauna diversity along land-use intensity gradients - Julia Köninger; Lukas Beule; Maria Tsiafouli; Julia Seeber; Helene Blasbichler; Jose Paul Sousa; Pedro Martins da Silva; Jan Frouz; Katarina Hedlund; Alberto Orgiazzi; Maria Jesús Iglesias Briones; Anton Potapov (Applied Soil Ecology, 2025)

The Disease Burden in Fish Farm Management: An Integrative View and a Specific Vision in Europe - Francesc Padros; Hamish Rodger; Maria Constenla; Ana Herrero; Maurice Glucksman; Alberto Allepuz; Carlos Zarza (Reviews in Aquaculture, 2025)
In aquaculture, the interactions and balance—or imbalance—between the fish, the rearing environment, pathogens, and farm management determine the occurrence and impact of clinical diseases. The global assessment of the factors related to disease impact is commonly referred to as disease burden. This assessment goes beyond the economic consequences of mortality and morbidity, encompassing additional economic factors related to disease management, as well as broader social and political consequences. The concept of disease burden is gaining relevance in aquaculture, where disease poses serious threats to animal welfare, productivity, and economic sustainability. At the farm level, the consideration of fish as living assets includes aspects such as direct mortality, indirect effects of mortality, and morbidity. Furthermore, the impact of disease on key performance indicators, routine operations, and planned productivity are important consequences. Diseases on fish farms also require effective management, whether through the implementation of treatments or through preventive and biosecurity measures, both of which can have indirect impacts that must be properly analyzed. In many cases, the risks associated with disease necessitate appropriate surveillance by farms or regulatory authorities, and the cost of such surveillance and insurances should be considered part of the overall disease burden. Other important aspects such as the impact on animal welfare, wellbeing of farm staff, integration of the concept into certification schemes, and issues related to social perception, acceptance, and prestige are also examined. In addition, macroeconomic factors such as market impacts, governance, and a special emphasis on the One Health approach are addressed.

Earthworm abundance increases aggregate stability: A field study in a Mediterranean agroforestry system - Filipa Reis; Eduardo Nascimento; Cristina Cruz; Teresa Dias; Katarina Hedlund; María J.I. Briones; Matty P. Berg; José Paulo Sousa; Pedro Martins da Silva (Applied Soil Ecology, 2025)

Modeling root water uptake patterns of oil crops grown on semiarid loess - Nana He; Xiaodong Gao; Lianhao Zhao; Pan Hu; Xining Zhao (Agricultural and Forest Meteorology, 2023)

Discoloration in the marine red algae Pyropia : causative factors and exploiting the biotechnological potential of a waste resource - Kichul Cho; Jina Heo; Sang‐Moo Lee; Jinwook Han; Hyun Dae Hong; Hancheol Jeon; Hyun‐Ju Hwang; Kyunghwa Baek; Jong Won Han (Reviews in Aquaculture, 2021)
Pyropia ( Porphyra , referred to as ‘Gim’ in Korea or ‘Nori’ in Japan), an economically valuable alga, has long been consumed as seafood, especially in north‐east Asian countries. Its well‐established conventional mass cultivation and harvesting methods in coastal areas widen the industrial availability of edible Pyropia sp. However, the unexpected discoloration derived from causative factors during the cultivation process gives rise to serious economic losses in the aquaculture industry. For the industrial use of discoloured laver waste (DLW), recent articles have suggested that DLW biomass could be used as a source of agar polysaccharide, porphyran, γ‐aminobutyric acid and other value‐added bioactive compound productions. Although DLW biomass has economic potential, the lack of integrated information and relevant studies still limits its industrial availability. Therefore, we discussed recent research concerning the functional ingredients, causative factors and potential availability of DLW to provide integrated information. Furthermore, this review suggested the potential industrial application of DLW as a source for other value‐added material production.

Epidemiology of marine gill diseases in Atlantic salmon ( Salmo salar ) aquaculture: a review - Annette S. Boerlage; Angela Ashby; Ana Herrero; Aaron Reeves; George J. Gunn; Hamish D. Rodger (Reviews in Aquaculture, 2020)
Gill disease of farmed Atlantic salmon ( Salmo salar ) in the marine environment has emerged as a significant problem for the salmon aquaculture industry. Different types of marine salmon gill disease reported include amoebic gill disease (AGD), parasitic gill disease, viral gill disease, bacterial gill disease, zooplankton (cnidarian nematocyst)‐associated gill disease, harmful algal gill disease and chemical/toxin‐associated gill disease. The term ‘multifactorial gill disease’ is used when multiple distinguishable types of disease (as opposed to an obvious single primary type) are present. When gill disease is non‐specific, it is referred to as ‘complex gill disease’ (CGD) or ‘complex gill disorder’. These two terms are often used interchangeably and are overlapping. The significance of many infectious and non‐infectious agents that may be associated with CGD is often unclear. In this review, we summarise aspects of the different types of gill disease that are relevant to the epidemiology of gill disease and of CGD in particular. We also tabulate simultaneously occurring putative pathogens to explore the multifactorial nature of gill disease.

The use of feed and water additives for live fish transport - Myriam Vanderzwalmen; Lewis Eaton; Carrie Mullen; Fiona Henriquez; Peter Carey; Donna Snellgrove; Katherine A. Sloman (Reviews in Aquaculture, 2019)
The transport of live fish for aquaculture, either for food or as companion animals, presents a major issue for animal welfare. The stressors associated with live transportation are well documented with a focus on maintaining water quality during transport to reduce stress. Far less considered is our ability to enhance health and welfare during transport through the use of dietary and water additives prior to and during transport. With increasing interest in the use of plant essential oils as feed additives in food fish aquaculture and the increased availability of products claiming to alleviate stress in ornamental species, there is a need for scientific investigation into these potential welfare‐promoting methods. Here, we summarise current knowledge on the use of food additives, water conditioners, antibiotics, antimicrobials and probiotics to promote fish health during transport. This review aims to highlight the gaps in our knowledge surrounding promising ways of promoting fish health during transport and to stimulate new research in this area.

Exercise training reduces the flesh firmness of juvenile hāpuku ( Polyprion oxygeneios ) with a hypertrophic reduction in muscle fibre density - JR Khan; S Pether; M Bruce; SP Walker; Y Hemar; NA Herbert (New Zealand Journal of Marine and Freshwater Research, 2015)
Consumers base the organoleptic quality of fish on factors such as texture, which can be altered by exercise. The effect of exercise on the fillet firmness of hāpuku ( Polyprion oxygeneios ) was investigated to determine whether exercise would yield a firmer and more desirable product. To achieve this, the firmness and muscle fibre density (MFD) of fillets from fish exercised for 8 weeks at 0.0, 0.75 or 1.5 body lengths/second (BL s −1 ) was assessed. Firmness was significantly lower in the 0.75 BL s −1 and 1.5 BL s −1 exercised fish than the 0.0 BL s −1 group. MFD was also significantly lower in the exercise treatments. This is explained by an increase in the median fibre size with exercise implying that exercise stimulated muscle fibre hypertrophy, leading to lowered MFD. Assuming that firmer flesh is perceived to be more desirable, exercise may have little value in the production of hāpuku.

Fish physiology and ecology: the contribution of the Leigh Laboratory to the collision of paradigms - NW Pankhurst; NA Herbert (New Zealand Journal of Marine and Freshwater Research, 2013)
The often pragmatic division of studies of function (physiology), and the regulation of distribution and abundance of organisms (ecology), as laboratory and field studies respectively, can create an unhelpful intellectual division that runs the risk of ignoring the interaction of physiology, behaviour and environment that regulates the lives of animals in the wild. This review examines the historical and current contribution of ecophysiological research conducted from the University of Auckland's Leigh Laboratory in bridging these paradigms, and generating new insights into animal function and community organisation. The assessment focuses on endocrine control processes, and metabolic and behavioural responses of fish to artificial and natural stressors, and examines tracks of future research needed to underpin understanding of likely effects of predicted environmental change on individuals and populations.